Sodium and calcium components of the action potential in a developing skeletal muscle cell line. - Kidokoro, Y (1975)
1. Developmental changes in action potential properties were studied in a clonal rat skeletal muscle cell line. 2. Small action potentials were evoked in mononucleate myoblasts. No spike was seen in Na-free saline. A similar spike was evoked in a medium where all NaCl was replaced by LiCl. No spike was evoked when NaCl was replaced by CsCl. 3. Action potentials overshot zero membrane potential in multinucleate myotubes. The action potential was composed of two components, an initial fast spike and a hump on the falling phase or in some cases a distinct second peak. 4. Teh overshoot of the initial fast spike decreased when the external Na concentration was decreased. 5. In saline with 10 mM-Ca the second component often formed a distinct peak following the initial fast spike. A slow regenerative potential was evoked in Na-free media with a depolarizing current pulse. 6. In saline containing BaCl-2 instead of CaCl-2 there was always a second peak, the overshoot of which changed with external Ba concentration. A slow regenerative potential was evoked in Na-free, Ba-saline. The membrane conductance at the peak of the Ba-action potential was larger than in the resting state. 7. In adult rat skeletal muscle, the shape of the action potential was not changed when Ca was replaced by Ba. No action potential was evoked in Na-free Ba-saline or Ba-saline with tetrodotoxin (3 times 10-7 M). 8. The significance of the Ca component in the developing muscle is discussed.